3-Total Edge Product Cordial Labeling for Stellation of Square Grid Graph. (6th December 2021) - Ullah, Rizwan; Rahmat, Gul; Numan, Muhammad; Anoh Yannick, Kraidi; Aslam, Adnan
Abstract : Let G be a simple graph with vertex set V G and edge set E G . An edge labeling δ : E G ⟶ 0, 1, …, p − 1, where p is an integer, 1 ≤ p ≤ E G, induces a vertex labeling δ ∗ : V H ⟶ 0, 1, …, p − 1 defined by δ ∗ v = δ e 1 δ e 2 ⋅ δ e n mod p, where e 1, e 2, …, e n are edges incident to v . The labeling δ is said to be p -total edge product cordial (TEPC) labeling of G if e δ i + v δ ∗ i − e δ j + v δ ∗ j ≤ 1 for every i, j, 0 ≤ i ≤ j ≤ p − 1, where e δ i and v δ ∗ i are numbers of edges and vertices labeled with integer i, respectively. In this paper, we have proved that the stellation of square grid graph admits a 3-total edge product cordial labeling.